Dictator's Instagram: personal and political narratives in a Chechen leader's social network. Issue 2 (4th May 2019) - Rodina, Elena; Dligach, Dmitriy
ABSTRACT: The purpose of this study is to explore how social networks, Instagram in particular, can be utilized by an autocrat in order to construct and promote the image of a charismatic leader. To do so, we conduct a topic modelling of 6854 Instagram posts made by Ramzan Kadyrov, the dictatorial head of the autonomous Chechen Republic in the Russian Federation. We then analyze the verbal framing of 24 dominant topics. The study concludes that the main rhetorical device that Kadyrov employs is a merging of personal and political themes throughout his posts. He personalizes political discussion by discussing public interest topics through the prism of his own personal life, and inserts political discourse into personal, intimate posts about his family, pastimes, and friends. The study shows that this tactic, often understood by media researchers as an oppositional device for harnessing popular support against an autocratic state, can be just as successfully employed by an autocratic leader. Kadyrov, who in his Instagram combines the tactics of a populist politician and an internet celebrity, has shaped a personality that can be best described as a "flirting populist" (Vezjak, Boris. 2018. "Dobro zmaguje: predsednik kot krščanski populist." In Media Res (personal blog), https://vezjak.com/2018/01/02/dobro-zmaguje-predsednik-kot-krscanski-populist/), which, as we suggest, is a new, online technology-enhanced type of a political figure.